Genome-wide association study and functional analysis of feet and leg conformation traits in Nellore cattle - Vargas, Giovana [UNESP]; Neves, Haroldo H. R.; Camargo, Gregório Miguel F.; Cardoso, Vânia; Munari, Danísio P. [UNESP]; Carvalheiro, Roberto [UNESP] (Oxford University Press (OUP), 2018)
Feet and leg conformation is evaluated as a subset of conformational structure traits in dairy and beef cattle and is related to the feet and leg quality that can compromise the animals’ productive performance and longevity. The aim of this study was to perform a genome-wide association study (GWAS) of two traits related to feet and leg conformation in Nellore cattle to identify chromosomal regions related to the expression of these traits. Phenotypic and pedigree data from 104,725 animals and genotypes from 1,435 animals and 407,730 SNPs were used. Feet and leg structure was evaluated as a binary trait (FL1) to identify yearling animals with feet and leg problems or as categorical score (FL2) to assess the overall quality of their feet and leg. The top ten 1-Mb windows that explained the largest proportion of the total genetic variance were identified and functional enrichment analyses were performed. The 10 windows with large effects obtained for FL1 are located on chromosomes 1, 2, 6, 7, 8, 10, and 14, and together explained 8.96% of the additive genetic variance. For FL2, these windows are located on chromosomes 1, 7, 10, 11, 18, 20, 22, 28, and 29, explaining 8.98% of the additive genetic variance. Several candidate genes were identified, including DLX2 which is associated with osteogenic differentiation, IL-1β and IL-1A associated with some properties of articular cartilage, PiT1 which plays an important role in bone physiology, and CTSL associated with rheumatoid arthritis. The results presented here should contribute to a better understanding of the genetic and physiologic mechanisms regulating both traits, and identifies candidate genes for future investigation of causal mutations.
Keywords: Beef cattle; Bos taurus indicus; Candidate genes; Weighted single step GBLUP